2009
DOI: 10.1200/jco.2008.21.6283
|View full text |Cite
|
Sign up to set email alerts
|

Association of Molecular Markers With Toxicity Outcomes in a Randomized Trial of Chemotherapy for Advanced Colorectal Cancer: The FOCUS Trial

Abstract: These results do not support the routine clinical use of the evaluated polymorphisms, including UGT1A1*28. Further investigation of XRCC1, ERCC2, and GSTP1 as potential predictors of irinotecan toxicity is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 31 publications
0
91
2
Order By: Relevance
“…Genotypes were determined by polymerase chain reaction (PCR)-based assays (restriction fragment length polymorphism (RFLP) and/or real-time) according to published methods. [11][12][13][14] or as recommended by the manufacturer. Positive and negative controls were included in each reaction as quality control.…”
Section: Genotyping Analysismentioning
confidence: 99%
“…Genotypes were determined by polymerase chain reaction (PCR)-based assays (restriction fragment length polymorphism (RFLP) and/or real-time) according to published methods. [11][12][13][14] or as recommended by the manufacturer. Positive and negative controls were included in each reaction as quality control.…”
Section: Genotyping Analysismentioning
confidence: 99%
“…Differences in toxicities experienced and responses in patients who have received the same chemotherapy agent or regimen are commonly observed [10,11], and these are likely to be a result of polymorphic genetic variation in genes involved in drug metabolism and DNA repair and apoptosis [5,12]. Recently, numerous clinical studies have elucidated that genes involved in drug transportation, drug metabolism, DNA repair, and apoptosis may modulate platinum-based chemotherapeutic efficacy and drug-related toxicity outcomes [13,14]. Therefore, the identification of genetic markers may enable us to predict the toxicity outcome with platinum-based chemotherapy and select optimal regimens for personalized therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis reported that although the toxicity relationships were much stronger with the UGT1A1 Ã 28 homozygous variant, associations were also found with the UGT1A1 Ã 28 heterozygous variant (21). At least three prospective randomized phase III trials (22)(23)(24), however, did not confirm these initial results, suggesting that the influence of the UGT1A1 Ã 28 allele on the toxicity of irinotecan is modest and that its assessment should not be mandatory in routine clinical practice (23).…”
Section: Discussionmentioning
confidence: 63%